2012
DOI: 10.1074/jbc.c112.406975
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian de Novo DNA Methyltransferases DNMT3A and DNMT3B Are Also DNA 5-Hydroxymethylcytosine Dehydroxymethylases

Abstract: Background:The pathways of DNA dehydroxymethylation and demethylation are yet to be better defined. Results: De novo DNMTs could serve as redox state-dependent DNA dehydroxymethylases. Conclusion: DNA dehydroxymethylation by DNMTs provides a simpler pathway to reduce DNA hydroxymethylation and methylation. Significance: That de novo DNMTs also function as DNA dehydroxymethylases raises intriguing new questions regarding their structures and regulatory roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
137
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 42 publications
2
137
1
3
Order By: Relevance
“…Observations made in vitro may explain this apparent paradox. Dnmt3a has been shown to function as a DNA demethylase under conditions of elevated Ca 2+ levels whereas the methyltransferase activity was reinstated after raising SAM levels (31)(32)(33). Induction of IEGs in DG neurons in vivo requires the opening of NMDA receptors, allowing a sustained rise in intracellular Ca 2+ levels (11).…”
Section: Discussionmentioning
confidence: 99%
“…Observations made in vitro may explain this apparent paradox. Dnmt3a has been shown to function as a DNA demethylase under conditions of elevated Ca 2+ levels whereas the methyltransferase activity was reinstated after raising SAM levels (31)(32)(33). Induction of IEGs in DG neurons in vivo requires the opening of NMDA receptors, allowing a sustained rise in intracellular Ca 2+ levels (11).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Interestingly, Chen et al found that the de novo methyltransferases DNMT3a and DNMT3b act as both DNA methyltransferases and DNA dehydroxymethylases, depending upon the redox environment: treatment with dithiothreitol (DTT) or hydrogen peroxide (H 2 O 2 ) inhibited and enhanced the dehydroxymethylation activities of the enzymes, respectively. 30 Chen et al speculated that the dual methylation and dehydroxymethylation activities of the DNMT3 enzymes might explain the paradoxical observation that DMNT3 expression is upregulated and gene-specific DNA methylation is increased in cancer cells, yet global DNA methylation is decreased. 30 Histone deacetylase (HDAC) inhibition has been shown experimentally to induce DNA hypomethylation, 31 and it has been hypothesized that HDAC activities might also be influenced directly by cellular redox.…”
Section: Discussionmentioning
confidence: 99%
“…30 Chen et al speculated that the dual methylation and dehydroxymethylation activities of the DNMT3 enzymes might explain the paradoxical observation that DMNT3 expression is upregulated and gene-specific DNA methylation is increased in cancer cells, yet global DNA methylation is decreased. 30 Histone deacetylase (HDAC) inhibition has been shown experimentally to induce DNA hypomethylation, 31 and it has been hypothesized that HDAC activities might also be influenced directly by cellular redox. 32 In human neuroblastoma cells, exposure to H 2 O 2 induces global DNA hypomethylation, along with downregulation of HDAC3, DNMT1 and DNMT3a expression.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT3A and DNMT3B are de novo DNA methyltransferases, and together with the maintenance methyltransferase DNMT1 are necessary for DNA methylation essential for embryonic development (Li et al, 1992, Okano et al, 1999. Other functions for these enzymes have been reported recently, but will not be discussed here (Chen et al, 2012). In germ cells, DNMT3L is expressed in testes at the stage of de novo methylation, and interacts with DNMT3A and B (Bourc'his and Bestor, 2004).…”
Section: Dna Methylation Development and Cancermentioning
confidence: 99%